The efficacy of municipal spatial plans implementation towards mitigating climate change : South African institutional challenges - Mokgotho, K. D.; Mokoele, N. J. (International Conference on Public Administration and Development Alternatives, 2020)
The purpose of the paper is to debate the efficacy of municipal spatial plans implementation towards climate change mitigation in urban areas. Post 1994 in South Africa, municipal spatial plans have been very integral towards shaping the growth of most cities and the facilitation of urban renewal. The densification of urban population has resulted in multifaceted challenges such as informal settlements, intensive energy consumption, traffic congestion, and increased greenhouses gas (GHGs) emissions. Spatial plans provide cities with the potential to address the increasing emissions which contribute to climate change through the process of urban renewal which helps improve the environmental condition. Therefore, the effective implementation of municipal spatial plans has a notable potential of significantly contributing towards climate change mitigation through the provision of energy efficient settlements, sustainable transport modes, improved urban planning and renewal, and the usage of renewable energy resources. The efficiency in the implementation of municipal spatial plans informs sustainable transport to reduce emissions. However, within the context of spatial planning, environmental protection and preservation mechanisms include, inter alia, the measures to mitigate climate change. Section seven (7) of the Spatial Planning and Land Use Management Act (SPLUMA) No. 16 of 2013 stated that plan-making and implementation processes should be designed in a manner that aims to mitigate negative environmental impacts such as climate change. However, it is often difficult to balance the trade-offs between the competing ideologies during implementation of the urban planning process and urban renewal. The paper is purely conceptual and relied largely on the review of existing literature to underpin the argument and accentuate the efficacy of municipal spatial plans implementation towards climate change mitigation. The paper concludes that for municipal spatial plans, which encompass urban planning and urban renewal, to be implemented effectively in an attempt to mitigate climate change, there must be proper coordination and alignment of policies and plans of diverse sectors such as housing, transportation and energy to reduce emissions
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Cities; Climate change; Spatial plans; Urbanisation; Urban Planning; SPLUMA; Economic development; Climatic changes -- South Africa